Spatial clustering of drug-resistant tuberculosis in Hunan province, China: An ecological study - Alene, Kefyalew; Xu, Z.; Bai, L.; Yi, H.; Tan, Y.; Gray, D.; Viney, K.; Clements, A.C.A. (BMJ PUBLISHING GROUP, 2021)
Objective: This study aimed to investigate the spatial distribution of drug-resistant tuberculosis (DR-TB) in Hunan province, China.